Investigating the readability of state-based formal requirements specification languages - Zimmerman, Marc K.; Lundqvist, Kristina; Leveson, Nancy (Proceedings - International Conference on Software Engineering, 2002)
The readability of formal requirements specification languages is hypothesized as a limiting factor in the acceptance of formal methods by the industrial community. An empirical study was conducted to determine how various factors of state-based requirements specification language design affect readability using aerospace applications. Six factors were tested in all, including the representation of the overall state machine structure, the expression of triggering conditions, the use of macros, the use of internal broadcast events, the use of hierarchies, and transition perspective (going-to or coming-from). Subjects included computer scientists as well as aerospace engineers in an effort to determine whether background affects notational preferences. Because so little previous experimentation on this topic exists on which to build hypotheses, the study was designed as a preliminary exploration of what factors are most important with respect to readability. It can serve as a starting point for more thorough and carefully controlled experimentation in specification language readability.